The Routledge Handbook of Taxation and Philanthropy - Peter, Henry; Lideikyte Huber, Giedre (Routledge International Handbooks, 2022)
The Routledge Handbook of Taxation and Philanthropy ventures into a territory that is still widely unexplored. It contains 30 academic contributions that aim to provide a better understanding of whether, why, and how philanthropic initiatives, understood as voluntary contributions for the common good, can and should be fostered by states through tax incentives. The topic has been addressed from a multidisciplinary and multicultural perspective - covering neuroeconomics, sociology, political science, psychology, affective sciences, philosophy, behavioral economy, and law - because of its global and multifaceted nature. It also contains the OECD report on Taxation and Philanthropy released in November 2020, which was prepared in this context as a result of a collaboration with the Geneva Centre for Philanthropy of the University of Geneva. The book is divided into four sections, exploring, respectively, the justification of tax incentives for philanthropy, theoretical and empirical insights about taxes, efficiency and donor behavior in that context, and tax incentives for cross-border philanthropy and for hybrid entities and social entrepreneurship. It is believed that this volume will be a landmark yet only the beginning of a journey in which a lot remains to be studied, learned, and said.